The Impact of Staff Turnover and Staff Density on Treatment Quality in a Psychiatric Clinic - Brandt, Wolfram A.; Bielitz, Christoph J.; Georgi, Alexander (Frontiers in Psychology, 2016)
Intuition suggests that improving stability of the health workforce brings benefits to staff, the organization and, most importantly, the patients. Unfortunately, there is limited research available to support this, and how health workforce stability can contribute to reduced costs and better treatment outcomes. To help to rectify this situation, we investigated the effects of staff turnover and staff density (staff members per patient) on the treatment outcome of inpatients in a psychiatric clinic. Our data come from the standard assessment of 1429 patients who sought treatment in our clinic from January 2011 to August 2013. Correlation analysis shows no significant effect of raw staff turnover (the total number of psychiatrists, physicians and psychologists starting or quitting work per month) on treatment quality. However, we do find two significant beneficial effects: First, a higher staff consistency (time without staff turnover) and second, a higher staff density lead to an improvement of treatment quality. Our findings underline the dire need for an extended effort to achieve optimal staff retention, both to improve patients outcomes and to reduce health expenses.